Whole Genome Sequencing and Characteristics of mcr-1–Harboring Plasmids of Porcine Escherichia coli Isolates Belonging to the High-Risk Clone O25b:H4-ST131 Clade B - Flament-Simon, Saskia-Camille; de Toro, María; Mora, Azucena; García, Vanesa; García-Meniño, Isidro; Díaz-Jiménez, Dafne; Herrera, Alexandra; Blanco, Jorge (Frontiers in Microbiology, 2020)
Porcine Escherichia coli ST131 isolates are scarcely documented. Here, whole genome sequencing, core genome (CG) and plasmidome analysis of seven isolates collected from diarrhoeic piglets and four from pork meat was performed. All of the 11 ST131 isolates belonged to serotype O25b:H4 and clade B, and showed fimH22 allele or mutational derivatives. The 11 porcine isolates possessed virulence traits that classified the isolates as avian pathogenic, uropathogenic and extraintestinal pathogenic E. coli like status (APEC, UPEC and ExPEC like) and constituted virotype D. The CG was performed for all porcine isolates in addition to 73 ST131 reference isolates from different origins. Within clade B the CG showed nine sub-clusters, allowing us to describe five new subclades (B6, B6-like, B7, B8, B9). There was an association between subclade B6, PST43, virotype D2 and food origin, while subclade B7 included PST9 isolates with virotype D5 from diarrhoeic piglets (p-value=0.007). The distance between human and porcine isolates from subclades B6 and B7 had an average of 20 SNP/Mb and 15 SNP/Mb, respectively. [F2:A-:B1]-IncF, ColE1-like and IncX plasmids were the most prevalent. Besides, IncF plasmids harboured a ColV region frequent among APEC isolates. Antimicrobial resistance genes conferring resistance to penicillin, tetracycline, quinolones and colistin were the most common. The mcr-1.1 gene was detected in 5 of 11 porcine isolates, integrated into the chromosome of one isolate and into plasmids in the remainder isolates (two MOBH11/IncHI2-ST4, one MOBP3/IncX4 and one MOBF12/IncF [F2:A-:B1] supposedly cointegrated with an IncHI2). The surrounding environments of the mcr-1 cassette showed variability. However, there were conserved structures within the same plasmid family. In conclusion, CG analysis defined five new subclades. The ST131 porcine isolates belonged to new subclades B6 and B7. Moreover, porcine and clinical human isolates were strongly related. The 11 porcine ST131 isolates harboured a wide variety of plasmids, virulence and resistance genes. Furthermore, epidemic plasmids IncX4 and IncHI2 are responsible for the acquisition of mcr-1.1 gene. We hypothesize that the APEC-IncF plasmid acquired the mcr-1.1 gene via cointegrating an IncHI2 plasmid, which is worrying due to combination of virulence and resistance attributes in a single mobile genetic element.